Evolution of the True Contact Area of Laser Textured Tungsten Under Dry Sliding Conditions - Lechthaler, Björn; Ochs, Georg; Mücklich, Frank; Dienwiebel, Martin (Frontiers in Mechanical Engineering, 2019)
Despite the great importance of the real contact area, it is a parameter which, depending on the tribological system, is difficult or impossible to obtain experimentally. In this work, a combination of methods is used to experimentally measure the development of the real contact surface and the results are compared with the friction coefficient course. The measurements were carried out with a home built in-situ tribometer, which records a 3D image of the surface after each individual friction cycle. A tungsten sample used was treated by laser interference with a line-like pattern to produce a deterministic surface. This allows to track the real contact area more precisely, in addition with the use of an inert corundum sphere as a counterbody. The real contact area was calculated from the height information obtained using a contact application. Finally the true contact surface was compared with the parallel recorded friction values. After a short running-in phase, the friction behaviour and the real contact surface showed a comparable course. This indicates that the changes in the real contact area could explain the friction behavior of the laser patterned sample and the methodology was proven to be suitable for determine the real contact area experimentally.